Training in Skills and Local Economic Development: Impact on restaurants in Playa Las Glorias in Northwestern Mexico - Juarez Martinez, Bertha Edith; Zúñiga-Espinoza, Nicolás Guadalupe; Zúñiga-Soto, Erick (Technium Social Sciences Journal, 2023)
The purpose of this work is to review an object of study: the restaurants of Playas Las Glorias, a tourist place located in the northwest of Mexico, in Guasave Sinaloa. To this end, a literature review on local economic development, skills training and tourism was carried out. The mixed design of the research allowed the collection of data through surveys and interviews with key informants and were processed through the R software. The data was collected from the total number of restaurants that exist in the said seashore. The results show the need to have better tools for the administration of the production units to continue attracting local, national and international tourism, coupled with the fact that it was evidenced that they impact the local economic development due to employment and wages generated for the population that lives close to this beautiful beach.